Natural variation for carotenoids in fresh kernels is controlled by uncommon variants in sweet corn. Issue 1 (24th April 2020) - Baseggio, Matheus; Murray, Matthew; Magallanes‐Lundback, Maria; Kaczmar, Nicholas; Chamness, James; Buckler, Edward S.; Smith, Margaret E.; DellaPenna, Dean; Tracy, William F.; Gore, Michael A.
Abstract: Sweet corn ( Zea mays L.) is highly consumed in the United States, but does not make major contributions to the daily intake of carotenoids (provitamin A carotenoids, lutein and zeaxanthin) that would help in the prevention of health complications. A genome‐wide association study of seven kernel carotenoids and twelve derivative traits was conducted in a sweet corn inbred line association panel ranging from light to dark yellow in endosperm color to elucidate the genetic basis of carotenoid levels in fresh kernels. In agreement with earlier studies of maize kernels at maturity, we detected an association of β ‐carotene hydroxylase ( crtRB1 ) with β‐carotene concentration and lycopene epsilon cyclase ( lcyE ) with the ratio of flux between the α‐ and β‐carotene branches in the carotenoid biosynthetic pathway. Additionally, we found that 5% or less of the evaluated inbred lines possessing the shrunken2 ( sh2 ) endosperm mutation had the most favorable lycE allele or crtRB1 haplotype for elevating β‐branch carotenoids (β‐carotene and zeaxanthin) or β‐carotene, respectively. Genomic prediction models with genome‐wide markers obtained moderately high predictive abilities for the carotenoid traits, especially lutein, and outperformed models with less markers that targeted candidate genes implicated in the synthesis, retention, and/or genetic control of kernel carotenoids. Taken together, our results constitute an important step toward increasing carotenoids in fresh sweet corn kernels.